Strategies to Improve Effectiveness of Rehabilitation Interventions for Street Children’s Social Development in Kakamega Central Sub-County, Kenya - Moses, Adama (2019)
Street children’s challenges are dynamic in nature. The study problem was the inadequacy of effective rehabilitation strategies that promote street children’s social development. The objective of the study was to determine strategies for improving effectiveness of rehabilitation interventions for street children social development in Kakamega Central Sub-county, Kenya. Evaluation research design was adopted. Study population included 220 street children in closed and open rehabilitation systems, 30 GOK and NGO’s rehabilitation staff, 10 social workers, 8 GOK officers, 5 counselors and 21 businessmen. Primary and secondary data were used. Primary data collection utilized questionnaires, interview guides, observation checklists and Focus Group Discussion. Cluster and snow-ball sampling were used to sample street children. Census and purposive sampling were used to sample key informants. Quantitative data was analyzed using descriptive statistics, specifically frequencies, percentages and mean. Inferential statistics were Chi- square test of independence and Spearman’s rank order correlation. Qualitative data analysis and interpretation utilized coding, voices and narrative analysis. Data was displayed in form of graphs, charts and tables. This study established that, 191(87%) of key informants and street children indicated that rehabilitation interventions should be improved. Strategies to improve effectiveness of rehabilitation interventions were; establish a listening platform for stakeholders and beneficiaries’ views in street children rehabilitation programmes 56(25.6%); establish a comprehensive rehabilitation and dropping centre for street children 31(13.9%); start Income Generating Activities in street children interventions 28(12.6%) while 10(4.7%) insisted on the improvement on education services and employable vocational skills training. There is a weak positive and insignificant relationship between open system rehabilitation intervention and sustainability strategy (ϒ=0.086, ᾳ=0.468, ρ-value=0.05). This implies that open system rehabilitations interventions are sustainable to a less degree. On the other hand there is a positive and significant relationship between closed system rehabilitation interventions and sustainability strategy (ϒ=0.470, ᾳ=0.000, ρ-value=0.05). This implies that closed system interventions are more sustainable as compared to the open rehabilitation systems. Therefore closed system rehabilitation interventions may have greater effectiveness on the street children’s social development. Keywords: Street children, Effective interventions, Social development and Rehabilitation strategies DOI: 10.7176/PPAR/9-6-05 Publication date:June 30th 201